If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + (t + 3)(-3) = t + -3 Reorder the terms: t + (3 + t)(-3) = t + -3 Reorder the terms for easier multiplication: t + -3(3 + t) = t + -3 t + (3 * -3 + t * -3) = t + -3 t + (-9 + -3t) = t + -3 Reorder the terms: -9 + t + -3t = t + -3 Combine like terms: t + -3t = -2t -9 + -2t = t + -3 Reorder the terms: -9 + -2t = -3 + t Solving -9 + -2t = -3 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. -9 + -2t + -1t = -3 + t + -1t Combine like terms: -2t + -1t = -3t -9 + -3t = -3 + t + -1t Combine like terms: t + -1t = 0 -9 + -3t = -3 + 0 -9 + -3t = -3 Add '9' to each side of the equation. -9 + 9 + -3t = -3 + 9 Combine like terms: -9 + 9 = 0 0 + -3t = -3 + 9 -3t = -3 + 9 Combine like terms: -3 + 9 = 6 -3t = 6 Divide each side by '-3'. t = -2 Simplifying t = -2
| p=-1.555555556 | | -4(4y-9)+2(2y+9)= | | 6y-9=13y+40 | | -275(-3x-5)=-5.75(1-2x) | | x^2-12x-180=0 | | d+6=6+d | | -0.34(3x-1)=0.28(3-4x) | | 9x-(4x-5)=50 | | -0.6(2x+5)=1.1(3-3x) | | 3+9z=6+6z-2+3z | | 81s^2+36s+4= | | 7r+4=0 | | 7r+7=0 | | t-(2t+3)=-1 | | 2(5a-3)-(4a-2)=-17-(4a-3) | | -12-(-10)= | | -12-(10)= | | 8-2(3x-5)=3(2x-1)+5 | | 2500=1000xX-800 | | 13x+17y=555 | | 2.2-8.3x=5.7 | | -12x^2+42x=0 | | 4(y+3)-(4y-2)=4(4y+3)+18 | | 3(3u-5)=39 | | 2500=2000xA-800 | | 1x-2y=1 | | 2(8y-4)=8y | | 1x-1y=2 | | 100(.018x+0.09y)=100(360)(0.16) | | 2x^3+1x^2+8x= | | x^2+3xy-10y^2=0 | | 22=6+2d |